PREPARATION AND CHARACTERIZATION OF MESOPOROUS SILICA NANOPARTICLES OF POORLY WATER SOLUBLE DRUG CANDIDATE IRBESARTAN AND FORMULATION OF IMMEDIATE RELEASE TABLETS - PAWDE MANIK SAMBHAJI; WADHER SJ; KALYANKAR TM (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present study aimed to prepared mesoporous silica nanoparticle (MSN)-loaded immediate release tablet of drug candidate irbesartan. This approach initiates immediate dissolution of poorly water soluble drug and increases solubility, respectively. Methods: According to this study, mesoporous nanoparticles could be used to assess a mesoporous carrier’s effectiveness for a drug candidate that is not poorly water soluble. To deliver a drug candidate with low water solubility, mesoporous nanoparticles were chosen. MSNs were prepared by sol-gel process. To describe the characteristics of mesoporous nanoparticles, we used scanning electron microscopy, infrared, differential scanning calorimetry, and powder X-ray diffraction. The percentage of drug release was observed by in vitro dissolution. Direct compression method was employed to formulation of immediate release tablets of mesoporous silica nanoparticle’s loaded irbesartan. Results: The particle size of MSN’s was found to be 98.3 nm. Brunauer-Emmett-Teller isotherm gives the idea about mesoporous nature with pore diameter 3.17 nm. The entrapment efficiency of drug into nanoparticles found to be 82%. Drug loaded MSNs then subjected to formulation of tablet by direct compression method. Irbesartan MSNs tablet was prepared successfully. The prepared tablet is white rounded in shape. The hardness of tablet is 3.21±0.117–4.32±0.620 range. The friability study showed that there is very little dusting of prepared that after 30 min of study. The disintegration time found to be in range of 117±0.330–135±0.00 s. The dissolution study drug is range of 65–80% in 45 min in acidic buffer pH 1.2. The Batch F1 showed lower release 68% and Batch F11 showed highest release of drug 81%. Conclusion: The MSNs loaded irbesartan immediate release tablet offers a sure alternative for immediate delivery of antihypertensive drug irbesartan. The MSNs enhance dissolution rate of drug and hence improved solubility which may give better therapeutic outcomes.